Is the universe transparent? - Liao, Kai; Avgoustidis, Anastasios; Li, Zhengxiang (American Physical Society, 2015)
We present our study on cosmic opacity, which relates to changes in photon number as photons travel from the source to the observer. Cosmic opacity may be caused by absorption or scattering due to matter in the Universe, or by extragalactic magnetic fields that can turn photons into unobserved particles (e.g., light axions, chameleons, gravitons, Kaluza-Klein modes), and it is crucial to correctly interpret astronomical photometric measurements like type Ia supernovae observations. On the other hand, the expansion rate at different epochs, i.e., the observational Hubble parameter data H (z), are obtained from differential ageing of passively evolving galaxies or from baryon acoustic oscillations and thus are not affected by cosmic opacity. In this work, we first construct opacity-free luminosity distances from H (z) determinations, taking into consideration correlations between different redshifts for our error analysis. Moreover, we let the light-curve fitting parameters, accounting for distance estimation in type Ia supernovae observations, free to ensure that our analysis is authentically cosmological-model independent and gives a robust result. Any nonzero residuals between these two kinds of luminosity distances can be deemed as an indication of the existence of cosmic opacity. While a transparent Universe is currently consistent with the data, our results show that strong constraints on opacity (and consequently on physical mechanisms that could cause it) can be obtained in a cosmological-model-independent fashion.